Edukasi Tentang Pemanfaatan Internet dan Teknologi Internet Of Things (IoT) di Kelurahan Padang Matinggi, Kecamatan Rantau Utara - Riszki Fadillah; Intan Nur Fitriyani (STIKES Columbia Asia Medan, 2025)
The utilization of internet technology and the Internet of Things (IoT) has become an integral part of various aspects of modern life, including the development of Community Social Worker (PSM) cadres' capacity. This study aims to provide education on the use of the internet and IoT to PSM cadres in Padang Matinggi Village, Rantau Utara Subdistrict, so they can optimize these technologies in supporting their social work activities. This community service activity is carried out through counseling and training that covers the basics of internet usage, the introduction of IoT concepts, and their application in social data management and community activities. The results of this activity showed a significant improvement in the participants' understanding of the technology provided, measured through pre-test and post-test evaluations. With a better understanding of technology, it is expected that PSM cadres can be more effective in performing their duties and contribute to improving the welfare of the community in Padang Matinggi Village.